PEMETAAN INDUSTRI PENGOLAHAN PANGAN UNGGULAN BERBASIS SISTEM INFORMASI GEOGRAFIS PADA PROPINSI JAWA TENGAH - Teddy Oswari; Fenni Agustina; Emy Haryatmi; E. Susy Suhendra (Teknoin, 2016)
The emphasis of the agricultural industry in Indonesia lies in the program of increasing food security, agribusiness development and improving the welfare of farmers. The priority of food security in establishing the independence of farmers in maintaining local resources efficiently and optimally, so that resources can be utilized further. The objectives of the research are to mapping the leading food processing industry, the determination of the leading local resources, the formation of documentation and the making of Geographic Information System (GIS) application to support the improvement of food processing industry in order to independence and food security, the growth and development of food industry in the region. The method of conducting research with data collection of food processing industry in Central Java Province by making data base and taxonomy, mapping of food processing industry in regency/city and making of digital portal with feature of data component of food processing industry to more introduce superior food processing industry to the public. The achieved results are documentation of leading food processing industry and GIS formation for all regencies/cities of Central Java Province, to encourage the improvement of food processing industry, real industrial income, processing quality and increasing self-sufficiency of food processing industry.